The Impact of Using Pictures on the Students’ Vocabulary Mastery at Grade Three of SD Negeri 2 Rulung Raya Natar South Lampung in Academic Year 2013-2014 - Surya Adi Tama (International Conference on Education and Language (ICEL), 2014)
The objective of this research was aimed to find out the impact of using pictures on the students’ vocabulary mastery at grade three of SD Negeri 2 Rulung Raya Natar South Lampung Academic year 2013 – 2014. Vocabulary mastery is defined as the students’ understandings on English words. Pictures were applied to increase the students’ vocabulary mastery which was low and limited. They were used as one of visual aids to help the students to master vocabulary and make them interested in learning English. Data were collected by incorporating two pre-tests and two post-tests in experimental group and control group. Treatment using Pictures was administered in experimental group, while control group received traditional teaching (TT). Data analysis was attempted using t-Test for two group design.Result indicated that p-value 1% = 2, 68, 5% = 2, 01, and t-value = 10, 15. It means p-value is smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The writer concluded that the application of using picture was more effective than traditional teaching.